A new species of Sceloporus of the torquatus group (Reptilia: Phrynosomatidae) from West Mexico - Flores-Villela, Oscar; Smith, Eric N.; Campillo-García, Gustavo; Martínez-Méndez, Norberto; Campbell, Jonathan A. (Zootaxa, 2022)
We describe Sceloporus huichol sp. nov., a new species of spiny lizard of the genus Sceloporus, that is found in the mountainous regions of Jalisco and Nayarit in western Mexico. The new species belongs to the torquatus species group and has previously been confused with Sceloporus melanogaster, from which it differs by its smaller size, head color and nuchal collar. Additionally, Sceloporus huichol sp. nov. is different from the rest of its congeners by relevant genetic and morphologicall data. Despite having a complete nuchal collar, characteristic of Sceloporus torquatus, S. huichol sp. nov. is more closely related phylogenetically to S. melanogaster. Recognition of this new species brings the number of species in the torquatus group to nine.